TOURISM SUSTAINABLE DEVELOPMENT CONCEPT: ECONOMY CONCILIATION, SOCIAL AND ENVIRONMENTAL DEVELOPMENT - Made Widya Paramitha (Universitas Triatma Mulya, 2022)
Beratan Lake tends to be changed negatively even various benefits are still there. If there is no attention and stakeholders contribution, this tourist destination will be forgotten by the future generations. Lake Beratan is one of natural resources which are really important to Bali as a water source which has a tight relationship with the religious because in each lake there are several temples in it to praise the God for the prosperity of the universe. Tourism brings the positive benefit for the local people and local government because tourism can generate the job opportunities, and also for the agricultural sector. Most the domestic tourists were interested to visit Lake Beratan for enjoy the water attraction which is offered around the lake. It is contrary with mostly the international tourists come to Lake Beratan for the natural, watch the religious ceremony at the temples in around the lake. Most respondents say that the environment of Lake Beratan extremely dirty, where there are a lot of rubbish everywhere. In addition, there are several pollutions that caused of the boating, parasailing activities and the expansion of parking area on the green belt of Lake Beratan. All stakeholders should concern immediately on the green belt of the lake, because the green belt of the lake is a part of the tourism area which should be protected to keep its sustainability. We can say that this tourism destination has the magnificent combination between nature and heritage. Thus, it could become a good place to develop sustainable development. Thanks to the tourism, it brings the valorization in the economic, social, and environment aspects. Nevertheless, in its development, all stakeholders should be involved together in each activities of tourism. And keep aware of the all effects that probably occurred by the tourism activities.